Rapid and accurate detection of Fusarium oxysporum f. sp. Lycopersici using one-pot, one-step LAMP-CRISPR/Cas12b method - Dai, Shijie; Wu, Yangsheng; Zhu, Na; Zhao, Yujin; Mao, Mingjiang; Li, Zheming; Zhu, Bo; Zhao, Weichun; Yuan, Xiaofeng (Frontiers in Plant Science, 2024)
IntroductionFusarium oxysporum f. sp. Lycopersici (Fol) is one of the most devastating plant pathogenic fungi, the causal agent of root rot for Atractylides macrocephala Koidz (AMK). An accurate rapid and convenient diagnosis for FoL detection is essential for determining management practices and preventing future losses for AMK.MethodsHere, we developed a novel method for Fol detection by integrating loop-mediated isothermal amplification (LAMP) assay and CRISPR/Cas12b detection in one-pot, and the whole reaction can simultaneously amplify and detect the target gene of Fol in one-step.ResultsThe total time of the present method is limited to 45 min and isothermally performed at 60°C. The limit of detection of this assay is 88.9 copies per reaction. The specificity of the LAMP-CRISPR/Cas12b method was 100% without any cross-reaction of other pathogens. A total of 24 nucleic acid samples were used to evaluate the performance of the LAMP-CRISPR/Cas12b method, including 12 with-Fol and 12 without-Fol. Compared with the gold standard results from real-time PCR, the present method provides a sensitivity of 100% (12/12), specificity of 100% (12/12), and consistency of 100% (24/24).DiscussionTogether, our preliminary results illustrated that the LAMP-CRISPR/Cas12b method is a rapid simple, and reliable tool for Fol diagnosis and could be applied in point-of-need phytopathogen detection.